Jinshin no hana as a communication strategy in batik tulis community development - Penina Inten (Faculty of Communications Science, Dr. Soetomo University, 2024)
Communication is of utmost importance in community development. Frequently, local community members find themselves marginalised from the communication processes integral to the advancement of their respective regions. As a result, they may fail to derive advantages from developmental initiatives and could fall prey to these transformations' repercussions. Employing the Jinshin no Hana approach as a communication strategy, the batik community in Pengilon Village is cultivated with a predominant emphasis on the local populace as the primary agents of change. Researchers serve as supporting components and facilitators for positive change. This approach is implemented through the utilisation of analytic area mapping and stakeholder analysis. Area mapping begins with assessing existing potentials by touring the village alongside local stakeholders to collect valuable initial data to be discussed with the stakeholders to formulate development ideas, followed by prioritisation using the pairwise method to be employed in the implementation phase. The implementation of Jinshin no Hana in Pengilon Village provides opportunities for the local community to actively engage in conveying ideas and the community's vision to the target audience. This serves as the groundwork for establishing a sustainable visual communication design process for Pengilon Village. This research can serve as a reference for future studies, emphasising the importance of not side-lining the local community as the primary figures in village development and the necessity to avoid assuming the role of instructors for them.